Shifting Global Economic Paradigm - Nwokoma, Okezie Goodluck; Idoko, Ms Uche; Ebere, James O'neal (International Journal of Sustainable Development & World Policy, 2013)
Due to the relevance of SMEs in the economy of the African continent, it is relevant to re-evaluate how best to apply financial and non-financial resources to the sector, to achieve its full potentials. The investment climate and business environment within which SMEs operate are very important indices in measuring their status. This survey has examined them in Lagos, Abuja and Port Harcourt, Nigeria.Huge potentials exist in each of the states in regards to the contributions of SMEs to their local economies. However, due to political instability, ethnic crises, crime and corruption, the status of SMEs in Nigeria is still at the primary stage. Large amounts of resources have been spent from own-country finances, and foreign aids. But ineffective programming and inefficient implementation of policies by national, state and Local Area Government agencies have left the investment in the firms without much profit.Current polices for SMEs provide financial, technical and logistic supports. However, these policies are only well-documented than acted upon. In some instances where government officials implement any policy, they are not directed to the small investors, but to the big ones and in some cases, such implementations are done on relationship basis. This practice succeeds in Nigeria because of corrupt legal systems and the refusal of SME operators to register and participate in the activities of unions and government agencies. Though there is a risk of undue interference by the officials of these bodies, but the progress of the firms hinges basically on structured and equitable distribution of available supports. Stand alone firms do not maximize the access to government supports. When every SME registers with and attends meetings of unions and government agencies that offer necessary services to it, such businesses will be well coordinated, operators will access available support facilities and there will be internal synergy within SMEs groups through knowledge sharing and mutual logistic support. Further, corrupt government officials will be constrained in executing such practices. This is because a union of SMEs will have a voice which can be heard and respected.